Pengaruh Variasi Minyak Daun Jeruk Purut Terhadap Sediaan Lotion Mengandung Gelatin Tulang Ayam dan Uji Aktivitas Antibakteri Staphylococcus aureus - Diyah Tri Utami; Diah Ayu Mustika Sari (Journal of Applied Agriculture, Health, and Technology, 2022)
Indonesia has a tropical climate, and it causes skin diseases such as acne. One of the bacteria causes acne is Staphylococcus aureus. Acne is caused by clogged skin pores so that oil secretion becomes clogged and then enlarges and dries. Antibacterial agents can be applied to the skin with the help of topical preparations, one of which is lotion. Lotion with kaffir lime leaf oil as the main ingredient contains high flavonoid compounds that have an antibacterial activity that can prevent acne, and chicken leg bone gelatin, contains collagen which can moisturize the skin. This research is experimental laboratory research. Lotion is made with different concentrations of kaffir lime leaf oil 0.5%, 1%, and 1.5% w/v. The lotion was tested for physical (organoleptic, homogeneity, spreadability, adhesion, viscosity) and chemical (pH) properties. Antibacterial activity test was carried out by well diffusion method. The research data were processed using SPSS 21 with the Kruskal Wallis Test. The test results showed that the lotion preparation with the strongest antibacterial activity was the preparation with 1.5% kaffir lime leaf oil, with a yield of 11.26 mm. The more composition of kaffir lime leaf oil, the stronger the antibacterial inhibition. The more composition of kaffir lime leaf oil causes the viscosity to decrease, the pH to increase, the adhesive power to decrease, the dispersion power to increase, and the bacterial inhibitory power to increase.